STUDI KEKUATAN FLEKSURAL ANTARA RESIN AKRILIK HEAT CURED DANTERMOPLASTIK NILON SETELAH DIRENDAM DALAM MINUMAN KOPI ULEEKARENG (Coffea robusta) - Iin Sundari; Pocut Aya Sofya; Millati Hanifa (Journal of Syiah Kuala Dentistry Society, 2016)
Heat-cured acrylic resin is the most common material used as denture base. Nowdays, thermoplastic nylon is also used as denture base material. One of the mechanical properties considered in the selection of denture base material is flexural strength. Flexural strength is affected by the absorption acid-containing fluid by the denture base material. Ulee Kareng coffee (coffea robusta) is a beverage that can be absorbed by the heat-cured acrylic resin and nylon thermoplastic and has acid content. The aim of this study is to observe the flexural strength of heat-cured acrylic resin and nylon thermoplastic after being immersed in Ulee Kareng coffee (Coffea robusta) for 7 days. This study is a laboratory experimental research with post-test only group design. The size of specimens were 60x10x2 mm and the total number of specimens were 16 which then divided into two groups. Group 1 consisted of 8 specimens of heat-cured acrylic resin (Meliodent) and group 2 consisted of 8 specimens of nylon thermoplastic (BIO TONE). After immersed in Ulee Kareng coffee (Coffea robusta), all specimens were tested for their flexural strength using Universal Testing Machine. The datas were analysed using unpaired t-test with significant p value of 0,05. Statistical analysis showed that the differences in flexural strength value were significant between heat-cured acrylic resin and nylon thermoplastic after being immersed in Ulee Kareng coffee (Coffea robusta). The conclusion of this study after being immersed in Ulee Kareng coffee (Coffea robusta), the flexural strength of thermoplastic nylon is higher than the flexural strength of heat-cured acrylic resin.Keywords : flexural strength, heat-cured acrylic resin, nylon thermoplastic, Ulee Kareng coffee (Coffea robusta)